Characterizing a novel in-situ oxygen delivery device for establishing controlled redox zonation within a high infiltration rate sequential biofilter. (1st September 2020) - Karakurt-Fischer, Sema; Bein, Emil; Drewes, Jörg E.; Hübner, Uwe
Abstract: By applying favorable oxic and oligotrophic conditions through subsequent aeration and an additional infiltration step, the sequential managed aquifer recharge technology (SMART) was proven to better remove trace organic chemicals (TOrCs) than conventional MAR systems. To minimize the physical footprint, pumping costs and hydraulic retention times, as well as to overcome limitations of site-specific heterogeneities of such systems, the SMART concept was further upgraded by two main engineered technologies. This SMART plus bioreactor is comprised of an infiltration trench and highly homogenous porous media to provide high infiltration rates and plug-flow conditions. Additionally, an in-situ oxygen delivery device, in particular a self-designed PDMS gas-liquid membrane contactor, was designed to establish favorable subsurface oxic conditions. This novel SMART plus technology was investigated at pilot scale and is designed for advanced water treatment either in the context of water reuse or treatment of impaired surface water. To determine the design specifications and to construct a pilot-scale membrane contactor, the mass transfer coefficients of the PDMS membrane were investigated at lab-scale for varying Reynold numbers (0.2–2). With the help of the customized membrane contactor, homogenous, bubble-free and passive oxygen delivery could be successfully demonstrated at pilot-scale under laminar flow conditions and short contact times. Oxygen concentrations downstream of the membrane contactors met the design specifications (>1 mg/L) as long as the required feed water quality was provided. However, high NH4 + concentrations in the secondary effluent resulted in higher and unsteady oxygen demand than the target oxygen transfer rates could meet and suboxic conditions prevailed. Although a 20–50% enhancement in the removal of certain compounds (4-FAA, antipyrine, sulfamethoxazole, and citalopram) was achieved, demonstration of the full potential of enhanced TOrC removal by SMART plus was hindered due to unsteady feed water quality. Graphical abstract: Image 1 Highlights: Novel biofilter using high rate infiltration trench & in-situ oxygen delivery. Minimizes the physical footprint, costs and impact of site-specific heterogeneities. Design of a pilot-scale PDMS gas-liquid membrane contactor. Successful, bubble-free and passive in-situ oxygen delivery into the subsurface. Effects of in-situ oxygen delivery and unsteady feed water quality on TOrC removal.